Public relations ethics in information management - Jakopović, Hrvoje (Journal of Education Culture and Society, 2020)
Public relations is involved in all communication between an organization and the pu-blic. In the contemporary world, PR practitioners have become the facilitators of information. Information and communication technology (ICT) have imposed new rules in the fi eld of public relations. Communication strategy and information management have become crucial parts of modern public relations. People change their habits with regard to the consumption of traditional and new media. The challenges imposed by the development of information and communication technology are also related to understanding the new information so-ciety. For that reason information ethics deals with the ethical implications of dissemination, use, development and safety of information. Public relations follow new information and communication trends, and they need to build fi rm ethical principles for the age of informa-tion. The author examines the ethical implications of the framing concept in public relations.